Kata Bahasa Indonesia Penanda Register Twitter: Suatu Kajian Morfologi - Rima Rismaya; Wahya Wahya; Fahmy Lukman (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
This study was conducted to describe the formation and meaning of Indonesian words as Indonesian Twitter's tweet register markers. This research is a qualitative descriptive study with data collection methods using listen and note method. The referential equivalent method and the content analysis method with the presentation of the results of data analysis carried out using formal and informal methods are two methods used in data analysis. The data source is Twitter user comments in the six tweets of the @areajulid account with the most comments in 2021. The results show that there are five ways of forming Indonesian words as Twitter registers, namely the process of (1) affixation, including the words